Le recours au dilemme éthico-professionnel pour enquêter sur l’identité professionnelle des enseignants de SVT lors de l’enseignement de la théorie de l’évolution - Benjamin Germann; Nathalie Panissal (Éducation et Socialisation)
French teaching curricula recommend the teaching of the theory of evolution. It is a pillar of the professional identity of SVT teachers. If the scientific consensus of this theory is strong, it can produce tensions or difficulties in the classroom, partly due to the interference between belief and knowledge: French secularism imposes neutrality on teachers, while demanding to favor the epistemic register, which may seem to be a paradoxical injunction. In this study, we submit SVT teachers to an ethical and professional dilemma. We wonder if resorting to this dilemma can bring tensions to the surface within their professional identity. Our results show that confronting this dilemma shakes up their professional identity.